2016
DOI: 10.18196/jgp.2016.0023
|View full text |Cite
|
Sign up to set email alerts
|

The Empowerment of Marginalized Community (Street Vendors) for Developing Creative Economy in Payakumbuh City West Sumatra

Abstract: This study generally aimed to find a model for empowerment of the marginalized community of street vendors for developing creative economy in Payakumbuh City, West Sumatra. While specifically this study aimed to get an overview of: 1) the City Government's efforts in the empowerment of street vendors, and 2) the degree of success of the empowerment program of street vendors by the City Government. This study uses qualitative approach. Data collected through questionnaire, interview, observation, and documentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Ardiyanti (2006) observed that the gathering of people doing exercise activity around a sports center has positively impacted the vendor selling beverages around the sports center. The revenue that can be gained by vending bikes around makeshift activities was estimated at US$ 13.47 to US$ 33.66 per day (Syamsir 2016), or equivalents of US$ 990 per month, which is greater than the city's minimum wage equivalents of US$ 270 per month.…”
Section: How the Citayam Pop-up And Makeshift Fashion Week (Cfw) Deve...mentioning
confidence: 97%
“…Ardiyanti (2006) observed that the gathering of people doing exercise activity around a sports center has positively impacted the vendor selling beverages around the sports center. The revenue that can be gained by vending bikes around makeshift activities was estimated at US$ 13.47 to US$ 33.66 per day (Syamsir 2016), or equivalents of US$ 990 per month, which is greater than the city's minimum wage equivalents of US$ 270 per month.…”
Section: How the Citayam Pop-up And Makeshift Fashion Week (Cfw) Deve...mentioning
confidence: 97%
“…There are some other studies on street vendors and traders conducted in any other city of Indonesia and any other developing country (Syamsir, 2016;Permatasari and Rudito;and Kumar, 2015). A study by Syamsir (2016) described the City Government's attempts to empower street vendors, and the degree of success of the empowerment program implemented by the Payakumbuh City Government of West Sumatra.…”
Section: Literature Review and Research Focusmentioning
confidence: 99%
“…A study by Syamsir (2016) described the City Government's attempts to empower street vendors, and the degree of success of the empowerment program implemented by the Payakumbuh City Government of West Sumatra. A study by Permatasari and Rudito (2014), using a quantitative method with multiple regression, examined factors affecting the successful implementation of street vendors relocation program including Business Location, Working Environment, Communication, Apparatus Behavior and Entrepreneurial Characteristic.…”
Section: Literature Review and Research Focusmentioning
confidence: 99%